2009
DOI: 10.1152/ajprenal.90319.2008
|View full text |Cite
|
Sign up to set email alerts
|

mTOR regulates expression of slit diaphragm proteins and cytoskeleton structure in podocytes

Abstract: Vollenbröker B, George B, Wolfgart M, Saleem MA, Pavenstädt H, Weide T. mTOR regulates expression of slit diaphragm proteins and cytoskeleton structure in podocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
3
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 45 publications
5
91
3
6
Order By: Relevance
“…has shown that phosphorylation of ERK1/2 regulates mTOR activation in different cell types (24,37,38). To elucidate the role of ERK1/2 in mTOR activation by TGF-␤1, ERK1/2 activation was inhibited by U0126 and PD184352, and 1 h of preincubation with these inhibitors significantly reduced mTOR and p70S6K phosphorylation by TGF-␤1 (Fig.…”
Section: Erk1/2 Regulates Tgf-␤1-induced Mtor Activation In a Tsc2-inmentioning
confidence: 91%
See 1 more Smart Citation
“…has shown that phosphorylation of ERK1/2 regulates mTOR activation in different cell types (24,37,38). To elucidate the role of ERK1/2 in mTOR activation by TGF-␤1, ERK1/2 activation was inhibited by U0126 and PD184352, and 1 h of preincubation with these inhibitors significantly reduced mTOR and p70S6K phosphorylation by TGF-␤1 (Fig.…”
Section: Erk1/2 Regulates Tgf-␤1-induced Mtor Activation In a Tsc2-inmentioning
confidence: 91%
“…Many growth factors, including insulin, insulin-like growth factor, and TGF-␤ and nutrients such as amino acids exert their cellular input through modulation of mTOR complexes (22,23). Akt, ERK1/2, and AMP-activated protein kinase are well known intermediate signaling molecules that transmit extracellular signals to mTOR (15,24).…”
mentioning
confidence: 99%
“…32 Torras et al also reported that rapamycin provoked significant increase in proteinrua in PAN. 33 These contradictory results against our present data might be evoked by the difference of the start point to treat cells and animals with mTOR inhibitor although both previous papers did not describe its start point in detail.…”
Section: Mtorc1 and Upr In Podocyte N Ito Et Almentioning
confidence: 92%
“…3 In certain cell types, including the podocyte, chronic inhibition of MTOR by rapamycin also results in downregulation of mTORC2 functions. [4][5][6] Although this mechanism of action has not been completely elucidated, data in podocytes suggest that prolonged rapamycin treatment directly downregulates MTOR and Rictor, both of which are required for mTORC2 function. 6 Sirolimus (rapamycin) was originally proposed as an immunosuppressant to prevent rejection of solid organ transplants.…”
mentioning
confidence: 99%